1981
DOI: 10.1108/eb038920
|View full text |Cite
|
Sign up to set email alerts
|

Looking at the Strategic Impact of Mergers

Abstract: American industry is in the midst of a new merger boom. Recent studies, however, show that such mergers do not necessarily enhance profits, boost productivity, aid efficiency, or result in social good. Given these findings, you ought to seriously question whether a proposed merger is a sound strategic decision before acting on it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Joint activity enables merging organizations to achieve economic, financial, and technological synergy, which contributes to their relative power (Pfeffer, 1972;Mueller, 1977;Bradley and Kom, 1984;Halpern, 1983;Jensen and Ruback, 1983;Lubatkin, 1983; Jemison and Sitkin, 1986). Merging thus aims to achieve growth, economies of scale, increased revenue and less cyclicity of income, greater market recognition, and wider dispersion (Davidson, 1981;Parsons and Baumgartner, 1970; Buono and Bowditch, 1989).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Joint activity enables merging organizations to achieve economic, financial, and technological synergy, which contributes to their relative power (Pfeffer, 1972;Mueller, 1977;Bradley and Kom, 1984;Halpern, 1983;Jensen and Ruback, 1983;Lubatkin, 1983; Jemison and Sitkin, 1986). Merging thus aims to achieve growth, economies of scale, increased revenue and less cyclicity of income, greater market recognition, and wider dispersion (Davidson, 1981;Parsons and Baumgartner, 1970; Buono and Bowditch, 1989).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent years the merger has become a common form of organizational change and since 1984, has affected over four million U.S. American workers annually (Marks, 1985(Marks, , 1986. In 1991 Mergers & Acquisitions reported that 54% of midsize business owners expect to make acquisitions in the next three to five years (Davidson, 1991). Clearly the decision to merge is an important element of organizational life, one that is creating dilemmas for literally millions of workers each year.…”
Section: Ideological Positioning In Organizational Change: the Dialecmentioning
confidence: 99%
“…The monograph is different from the traditional economic theory in two important aspects: first, it focuses on the growth of the production of heterogeneous products; second, it is a growth theory rather than an equilibrium theory [12]. These two aspects are necessary to understand the diversification of the company.…”
Section: Resource Theorymentioning
confidence: 99%